IMPROVING STUDENTS' MATHEMATICAL REASONING ABILITY THROUGH AUGMENTED REALITY LEARNING MEDIA - Lilis Marina Angraini; Muchamad Subali Noto; Aulia Sthephani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
This study is prompted by the insufficient mathematical reasoning skills among junior high school students in Pekanbaru. This information is gathered from reports by teachers indicating that students face challenges in adequately solving mathematical reasoning problems. The primary objective of this research is to assess the impact of augmented reality learning media on the mathematical reasoning abilities of students. The study employs an experimental approach with a quasi-experimental design involving random sampling, with randomization conducted at the class level. The research encompasses 60 seventh-grade students from one of the junior high schools in Pekanbaru during the academic year 2022/2023, with a focus on the geometry of flat shapes, particularly triangles and quadrilaterals. The assessment instrument utilized is a mathematical reasoning ability test constructed based on various indicators as per expert recommendations. Data analysis encompasses normality tests, homogeneity tests, and parametric tests. The results of the data analysis reveal a significance value of 0.00, signifying that the enhancement in students' mathematical reasoning abilities is more pronounced when utilizing augmented reality learning media compared to conventional learning methods.Penelitian ini dilatarbelakangi oleh rendahnya kemampuan penalaran matematis siswa SMP di Pekanbaru, hal ini diperoleh dari keterangan guru yang mengajar di sekolah bahwa anak-anak masih belum cukup mampu dalam menyelesaikan soal-soal penalaran matematis. Tujuan penelitian ini adalah untuk menganalisis pengaruh penggunaan media pembelajaran augmented reality terhadap kemampuan penalaran matematis siswa. Penelitian ini merupakan penelitian eksperimen dengan desain kuasi-eksperimen yang menggunakan sampel acak, namun pengacakan yang dilakukan adalah acak kelas. Subyek penelitian sebanyak 60 siswa kelas VII di salah satu SMP Pekanbaru tahun pelajaran 2022/2023 pada materi geometri bangun datar, khususnya segitiga dan segiempat. Instrumen yang digunakan adalah tes kemampuan penalaran matematis yang mengacu pada beberapa indikator menurut para ahli. Pengolahan data menggunakan uji normalitas, uji homogenitas, dan uji parametrik. Berdasarkan pengolahan data diperoleh signifikansi sebesar 0,00 yang mengindikasikan bahwa peningkatan kemampuan penalaran matematis siswa yang menggunakan media pembelajaran dengan augmented reality lebih baik daripada siswa yang belajar secara konvensional.